PERJUANGAN TOKOH PEREMPUAN DALAM MENGHADAPI DOMINASI PATRIARKI DALAM NOVEL SULUH RINDU KARYA HABIBURRAHMAN EL SHIRAZY: KAJIAN FEMINISM - Tita Adina; Elsa Mulya Karlina (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to analyze the struggle of female characters in facing patriarchal domination in the novel Suluh Rindu by Habiburrahman El Shirazy. The problem raised in this study is how patriarchal domination affects the lives of female characters, especially Syifa, and the form of struggle carried out to fight against existing gender inequality. This study uses a qualitative approach with a library research design. Data were collected through reading and note-taking techniques on the text of the novel Suluh Rindu, which were then analyzed using feminist theory, especially the perspective of Simone de Beauvoir. The results of the study show that Syifa experiences pressure from family and society that requires women to fulfill traditional roles, such as getting married and becoming a mother. However, Syifa chooses to reject the forced matchmaking and focuses on education, and maintains her life principles. This study shows that despite being trapped in a patriarchal system, the female characters in Suluh Rindu struggle to become active subjects who are free to determine their life path. These findings contribute to the study of Indonesian literary feminism and broaden the understanding of women's struggles in a patriarchal society.